Reborn of crisis : 9/11 and the resurgent superhero - Hagley, Annika, 1983-; Harrison, Michael, 1975- (Abingdon, Oxon ; New York : Routledge, 2020)
"This book examines the dominant popular culture convention of the superhero, situated within the most significant global event of the last twenty years. Exploring the explosion of the superhero genre post-9/11, it sheds fresh light on the manner in which American society has processed and continues to process the trauma from the terrorist attacks. Beginning with the development of Batman in comics, television and film, the authors offer studies of popular films including Iron Man, Captain America, The X-Men, Black Panther and Wonder Woman, revealing the ways in which these texts meditate upon the events and aftermath of 9/11, and challenge the dominant hyper-patriotic narrative that emerged in response to the attacks. A study of the superhero genre's capacity to unpack complex global interplays which question America's foreign policy actions and the white, militarized masculinity that has characterized major discourses following 9/11, this volume explores the engagement of superhero films with issues of authority, patriotism, war, morals, race, gender, surveillance, the military industrial complex, and American political and social identities. As such, it will appeal to scholars and students of cultural and media studies, film studies, sociology, politics and American studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Superhero films -- United States -- History and criticism; September 11 Terrorist Attacks, 2001, in motion pictures; September 11 Terrorist Attacks, 2001, in mass media; National characteristics, American, in motion pictures; Popular culture -- Political aspects -- United States -- History -- 21st century; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General